Various aspects of two treatment approaches to patients with problems of hypodontia of upper lateral incisors - Stojanović, Ljiljana; Galluccio, Gabriella; Todorović, Aleksandar; Lazić, Zoran; Tsolakis, Apostolos; Pajević, Tina (Vojnosanitetski pregled, 2022)
Introduction. The treatment of hypodontia of the upper lateral incisors could be orthodontic or multidisciplinary with combined orthodontic, surgical and prosthetic involvement. Both options have their pros and cons. They could be quite challenging to manage, particularly in the cases of unilateral missing of the upper lateral incisor in adult patients. We presented two cases with these different treatment approaches in young adult patients with unilateral missing of upper lateral incisors. Case report. The first case presents a combined orthodontic, surgical and prosthetic treatment of the missing upper right lateral incisor in an adult patient. Our clinical examination of a  22-year-old girl showed her missing tooth 12 with almost completely closed space, midline deviation, reduced overjet and overbite, Class III molar relationship on the right side and Class I molar relationship on the left side with V-shape maxillary arch and crossbite tendency in the frontal region. Based on the skeletal Class III relationship and intraoral findings, it was decided to open the space for tooth 12 and to establish the overjet, overbite and Class I occlusion as well. A surgical implant insertion followed the orthodontic preparation, with crown positioning after surgical healing. The second case described the orthodontic treatment of unilateral hypodontia in a young adult patient. Clinical and radiographic examinations of a 24-year-old female revealed hypodontia of tooth 12 with microdontic conical tooth 22 with severe crowding in the lower arch, Class I molar relationship on the right side and half-Class II relationship on the left side. The treatment decision was to extract atypical tooth 22, teeth 35 and 44 and to move the upper teeth forward to close the space. After the orthodontic treatment, upper canines were mesially moved to replace those missing lateral incisors. Conclusion. Both treatments successfully resolved malocclusion and obtained solid aesthetic and functional results. The treatment plan and decision to open or close the space in a case of hypodontia should be made individually for each patient according to their age, malocclusion, canines’ shape and size and patient preferences.
Keywords: anodontia; dental implants; incisor; malocclusion; orthodontics; orthodontics, corrective